Intra- and Extraluminal Structural and Functional Venous Anomalies in Multiple Sclerosis, as Evidenced by 2 Noninvasive Imaging Techniques - Dolic, K.; Marr, K.; Valnarov, V.; Dwyer, M.G.; Carl, E.; Karmon, Y.; Kennedy, C.; Brooks, C.; Kilanowski, C.; Hunt, K.; Siddiqui, A.H.; Hojnacki, D.; et al. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Chronic cerebrospinal venous insufficiency (CCSVI) is a vascular condition characterized by anomalies of the main extracranial cerebrospinal venous routes that interfere with normal venous outflow. Research into CCSVI will determine its sensitivity and specificity for a diagnosis of MS, its prevalence in MS patients, and its clinical, MRI, and genetic correlates. Our aim was to investigate the prevalence and number of intra- and extraluminal structural and functional extracranial venous abnormalities by using DS and MRV, in patients with MS and HCs. MATERIALS AND METHODS: One hundred fifty patients with MS, 104 (69.3%) with RR and 46 (30.7%) with a progressive MS course, and 63 age- and sex-matched HCs were scanned with 3T MR imaging by using TOF and TRICKS sequences (only patients with MS). All subjects underwent DS examination for intra- and extraluminal structural and functional abnormalities of the IJVs. Absent/pinpoint IJV flow morphology on MRV was considered an abnormal finding. Prominence of collateral extracranial veins was assessed with MRV. RESULTS: Patients with MS had a significantly higher number of functional (P < .0001), total (P = .001), and intraluminal (P = .005) structural IJV DS abnormalities than HCs. There was a trend for more patients with MS with extraluminal IJV DS abnormalities (P = .023). No significant differences were found on the MRV IJV flow morphology scale between patients with MS and HCs. Patients with progressive MS showed more extraluminal IJV DS abnormalities (P = .01) and more MRV flow abnormalities on TOF (P = .006) and TRICKS (P = .01) than patients with nonprogressive MS. There was a trend for a higher number of collateral veins in patients with MS than in HCs (P = .016). CONCLUSIONS: DS is more sensitive than MRV in detecting intraluminal structural and functional venous abnormalities in patients with MS compared with HCs, whereas MRV is more sensitive in showing collaterals. CCSVIchronic cerebrospinal venous insufficiencyCVcatheter venographyDSDoppler sonographyEDSSExpanded Disability Status ScaleGdgadoliniumHChealthy controlICCinterclass correlation coefficientIJVinternal jugular veinMRVMR venographyPPprimary-progressiveRRrelapsing-remittingSPsecondary-progressiveTOFtime-of-flightTRICKStime-resolved imaging of contrast kineticsVVvertebral veins